Sensitive and specific immunohistochemical diagnosis of human alveolar echinococcosis with the monoclonal antibody Em2G11. - Thomas F E Barth; Tobias S Herrmann; Dennis Tappe; Lorenz Stark; Beate Grüner; Klaus Buttenschoen; Andreas Hillenbrand; Markus Juchems; Doris Henne-Bruns; Petra Kern; Hanns M Seitz; Peter Möller; et al. (Public Library of Science (PLoS), 2012)
BACKGROUND: Alveolar echinococcosis (AE) is caused by the metacestode stage of Echinococcus multilocularis. Differential diagnosis with cystic echinococcosis (CE) caused by E. granulosus and AE is challenging. We aimed at improving diagnosis of AE on paraffin sections of infected human tissue by immunohistochemical testing of a specific antibody. METHODOLOGY/PRINCIPAL FINDINGS: We have analysed 96 paraffin archived specimens, including 6 cutting needle biopsies and 3 fine needle aspirates, from patients with suspected AE or CE with the monoclonal antibody (mAb) Em2G11 specific for the Em2 antigen of E. multilocularis metacestodes. In human tissue, staining with mAb Em2G11 is highly specific for E. multilocularis metacestodes while no staining is detected in CE lesions. In addition, the antibody detects small particles of E. multilocularis (spems) of less than 1 µm outside the main lesion in necrotic tissue, liver sinusoids and lymphatic tissue most probably caused by shedding of parasitic material. The conventional histological diagnosis based on haematoxylin and eosin and PAS stainings were in accordance with the immunohistological diagnosis using mAb Em2G11 in 90 of 96 samples. In 6 samples conventional subtype diagnosis of echinococcosis had to be adjusted when revised by immunohistology with mAb Em2G11. CONCLUSIONS/SIGNIFICANCE: Immunohistochemistry with the mAb Em2G11 is a new, highly specific and sensitive diagnostic tool for AE. The staining of small particles of E. multilocularis (spems) outside the main lesion including immunocompetent tissue, such as lymph nodes, suggests a systemic effect on the host.